Electronic structure and transport properties of 2D RhTeCl: a NEGF-DFT study. Issue 43 (22nd October 2019) - Qu, Hengze; Guo, Shiying; Zhou, Wenhan; Cai, Bo; Zhang, Shengli; Huang, Yaxin; Li, Zhi; Chen, Xianping; Zeng, Haibo
Abstract : Predicted through the density functional theory coupled with non-equilibrium Green's function method, 2D RhTeCl with promising electronic properties and device performances has the scope of becoming a potential candidate for the future low power devices. Abstract : 2D materials are considered as excellent candidates for next-generation electronic and optoelectronic devices. However, the corresponding systems with both an appropriate direct band gap and high carrier mobility are urgently required. Here, a new 2D semiconductor, monolayer RhTeCl, is investigated based on first-principles calculations. Monolayer RhTeCl possesses a direct band gap of 2.16 eV, with a high electron mobility up to 1.5 × 10 4 cm 2 V −1 s −1 . Thus, monolayer RhTeCl double-gated metal–oxide–semiconductor field-effect transistors (MOSFETs) with a 6 nm gate length are simulated by quantum transport methods. The 6 nm monolayer RhTeCl n-MOSFET displays a steep sub- kT / q switching characteristic and a high on/off ratio (10 6 ), which demonstrates a superior gate control. Therefore, these promising semiconductor characteristics and device performances of 2D RhTeCl provide new opportunities for novel low power ultra-scaled devices.